**By limit process, the derivative of a function f(x) is :-**

**f'(x) = lim h --> 0 [{f(x+h) - f(x)}/h]**

Now, the given function is :-

h(s) = 3 + (3/2)s

Thus, h'(s) = lim t --> 0 [{h(s+t) - h(t)}/t]

or, h'(s) = lim t ---> 0 [{{3 + (2/3)*(s+t)}...

## Unlock

This Answer NowStart your **48-hour free trial** to unlock this answer and thousands more. Enjoy eNotes ad-free and cancel anytime.

Already a member? Log in here.

**By limit process, the derivative of a function f(x) is :-**

**f'(x) = lim h --> 0 [{f(x+h) - f(x)}/h]**

Now, the given function is :-

h(s) = 3 + (3/2)s

Thus, h'(s) = lim t --> 0 [{h(s+t) - h(t)}/t]

or, h'(s) = lim t ---> 0 [{{3 + (2/3)*(s+t)} - {3 + (2/3)s}}/t]

or, h'(s) = lim t ---> 0 [{(2/3)t}/t] = 2/3